2019
DOI: 10.1101/844316
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural dysfunction correlates with heat coma and CTmax in Drosophila but does not set the boundaries for heat stress survival

Abstract: Running title: Neural dysfunction in heat stress 12 13 Summary statement 14Hyperthermic failure of the Drosophila central nervous system causes heat coma, a phenotype varying in 15 temperature between drosophilids, but neural failure is likely not the primary cause of heat mortality. 16 Abstract 17When heated, insects loose coordinated movement followed by the onset of heat coma (CTmax). These 18 phenotypes are popular measures to quantify inter-and intraspecific differences in insect heat tolerance, and 19CTm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…These included a cluster of functionally related genes (dar1, fru, NetA, RhoGEF64C, trio, twf) involved in nervous system development, which was reflected in overrepresentation of the nervous system and cell morphogenesis and differentiation GO categories in the CT min GWAS gene set. Neuronal failure operationally defines both CT min and CT max (Andersen et al, 2018;Andersen and Overgaard, 2019;Jørgensen et al, 2019), and dynamic stabilization of the neuromuscular circuit under temperature stress is a likely mechanism for altering thermal limits. Indeed, previous investigation of the genetic architecture of cold hardiness and electrophysiological analyses of the rapid hardening response both suggest an important role for stabilization of ion channels and cytoskeletal structures supporting the synapse and neuromuscular junction (Klose and Robertson, 2004;Robertson and Money, 2012;Freda et al, 2017).…”
Section: H3: Genes Involved In Thermal Tolerance Affect the Developmementioning
confidence: 99%
See 1 more Smart Citation
“…These included a cluster of functionally related genes (dar1, fru, NetA, RhoGEF64C, trio, twf) involved in nervous system development, which was reflected in overrepresentation of the nervous system and cell morphogenesis and differentiation GO categories in the CT min GWAS gene set. Neuronal failure operationally defines both CT min and CT max (Andersen et al, 2018;Andersen and Overgaard, 2019;Jørgensen et al, 2019), and dynamic stabilization of the neuromuscular circuit under temperature stress is a likely mechanism for altering thermal limits. Indeed, previous investigation of the genetic architecture of cold hardiness and electrophysiological analyses of the rapid hardening response both suggest an important role for stabilization of ion channels and cytoskeletal structures supporting the synapse and neuromuscular junction (Klose and Robertson, 2004;Robertson and Money, 2012;Freda et al, 2017).…”
Section: H3: Genes Involved In Thermal Tolerance Affect the Developmementioning
confidence: 99%
“…The few genes that consistently appeared in overrepresented categories, fra, fz2 and ptc, are also functionally associated with the nervous system, including axon and dendrite guidance and synapse organization. Spreading depolarization of the central nervous system (triggered by failure to maintain ion gradients between the intra-and extracellular compartments) is linked with heat tolerance across Drosophila species (Jørgensen et al, 2019), indicating that neuronal failure is an important component of heat tolerance in addition to cold tolerance. An additional set of three genes, Pax, sls and Zasp66, co-occurred in several associated categories of muscle structure and development ( Figure 5).…”
Section: H3: Genes Involved In Thermal Tolerance Affect the Developmementioning
confidence: 99%
“…Within voluntarily tolerated thermal levels, different aspects of physiological performance are optimized at different temperatures (e.g., stamina may be more optimized at lower temperatures than sprint speed, Huey et al 1984). Nonetheless, if body temperatures rise excessively, locomotor and neural processes eventually stop, and the animals reach their Critical Thermal Maximum (CT max , Cowles and Bogert 1944;Jørgensen et al 2020), which can kill them almost immediately (Angilletta et al 2007;Christian and Morton 1992;Ribeiro et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-induced neural dysfunction could consequently underlie upper thermal tolerance limits, either via direct thermal effects on neurons (11, 12) or via indirect thermal effects from oxygen limitations (18). Examples of severe heat-induced neural dysfunctions include spreading depolarizations in the brain of fruit flies (26), loss of rhythmic neural activity in the digestive system of the Jonah crab (27), and thermogenic seizures in vertebrates (2830). However, few studies have directly investigated how neural dysfunction relates to measurements of thermal tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have directly investigated how neural dysfunction relates to measurements of thermal tolerance. In fruit flies, spreading depolarizations measured in restrained flies occur at similar temperatures as a heat-induced coma in freely moving conspecifics (26). Similarly, goldfish lose equilibrium at temperatures that alters the activity of cerebellar neurons in anesthetized conspecifics (11), and a study on Atlantic cod found that cooling the brain marginally increased CT max , suggesting a causal link between brain function and thermal tolerance (12).…”
Section: Introductionmentioning
confidence: 99%